2019
DOI: 10.4330/wjc.v11.i12.292
|View full text |Cite
|
Sign up to set email alerts
|

Red blood cell distribution width: A marker of anisocytosis potentially associated with atrial fibrillation

Abstract: The incorporation of biomarkers in the actually used risk scores seem to be helpful for early identifying atrial fibrillation (AF) patients at higher risk. The aim of this critical review of the scientific literature is to investigate the potential clinical significance of red blood cell distribution width (RDW) in AF. A systematic electronic search was carried out to identify all articles describing an epidemiological association between RDW and AF in adult human populations. Data abstraction was conducted on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 71 publications
1
16
0
Order By: Relevance
“…Different factors have been associated with the outcome stroke such as oxidation [17,18], inflammation [19][20][21][22], hyperglycemia [23], or alterations in brain perfusion due to blood pressure variability [24,25]. In addition, there has been found the association of RDW with oxidative stress in animal models [26], with blood TNF-alpha levels in critically ill patients [27,28], and with atrial fibrillation and its risk of complications and mortality [29][30][31]. Another novel finding of our study was that there is a positive association between RDW and blood levels of malondialdehyde and TNF-alpha during the first week of MMCAI.…”
Section: Discussionmentioning
confidence: 99%
“…Different factors have been associated with the outcome stroke such as oxidation [17,18], inflammation [19][20][21][22], hyperglycemia [23], or alterations in brain perfusion due to blood pressure variability [24,25]. In addition, there has been found the association of RDW with oxidative stress in animal models [26], with blood TNF-alpha levels in critically ill patients [27,28], and with atrial fibrillation and its risk of complications and mortality [29][30][31]. Another novel finding of our study was that there is a positive association between RDW and blood levels of malondialdehyde and TNF-alpha during the first week of MMCAI.…”
Section: Discussionmentioning
confidence: 99%
“…An association between reduced erythrocyte deformability and cardiac arrhythmias has been demonstrated previously. 39 As addressed by a recent review, 40 anemia is associated with both AF development and increased RDW. 40 In the present study, risk estimates for AF were not significantly modified by adjusting for hemoglobin levels in the regression models, nor by excluding anemic participants from the multivariable analyses.…”
Section: Discussionmentioning
confidence: 99%
“…39 As addressed by a recent review, 40 anemia is associated with both AF development and increased RDW. 40 In the present study, risk estimates for AF were not significantly modified by adjusting for hemoglobin levels in the regression models, nor by excluding anemic participants from the multivariable analyses. Previous observational studies, including reports from the Tromsø Study, have reported an increased risk of both VTE 13,14 and ischemic stroke 11,12 by RDW in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…13,[15][16][17][18][19][20][21][22] RDW is a marker of anisocytosis of erythrocytes and is related to inflammatory and oxidative stress. 13,17 Interestingly, a relation of RDW with inflammatory and oxidative markers in an experimental model of atrial tachy-pacing has been demonstrated. 18 We have also previously published data indicating an association between baseline RDW levels and postoperative AF after cardiac operations.…”
Section: Introductionmentioning
confidence: 99%
“…19 Of note, recent systematic reviews and meta-analyses indicate that RDW is an independent predictor of AF in several clinical settings as well as a predictor of adverse outcomes and complications in AF patients. 13,17 On the other hand, increased activity of γGT is associated with increased oxidative stress and increased cardiovascular risk and mortality. 20 An increasing body of evidence indicates a significant association between increased γGT levels, within normal limits, and AF.…”
Section: Introductionmentioning
confidence: 99%